2016
DOI: 10.4253/wjge.v8.i10.395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic papillary balloon dilatation and endoscopic sphincterotomy for bile duct stones

Abstract: Endoscopic treatment for bile duct stones is low-invasive and currently considered as the first choice of the treatment. For the treatment of bile duct stones, papillary treatment is necessary, and the treatments used at the time are broadly classified into two types; endoscopic papillary balloon dilatation where bile duct closing part is dilated with a balloon and endoscopic sphincterotomy (EST) where bile duct closing part is incised. Both procedures have advantages and disadvantages. Golden standard is EST,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…According to most of the meta-analyses, the success rates of EST and EPBD for common bile duct stones were 94.3% and 96.5%, respectively 8 . The success rates of combining limited endoscopic sphincterotomy and balloon dilation in our study were 99.4% (3 min group) and 98.8% (1 min group), respectively, which were higher than those reported before, indicating that limited EST combined with balloon dilatation was effective for CBD stone removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to most of the meta-analyses, the success rates of EST and EPBD for common bile duct stones were 94.3% and 96.5%, respectively 8 . The success rates of combining limited endoscopic sphincterotomy and balloon dilation in our study were 99.4% (3 min group) and 98.8% (1 min group), respectively, which were higher than those reported before, indicating that limited EST combined with balloon dilatation was effective for CBD stone removal.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had found a relatively high incidence of pancreatitis after EPBD, especially when small (diameter ≤ 10 mm) balloon dilation was performed for small CBD stones (diameter ≤ 10 mm) 8 12 . Interestingly, it has been reported that the incidence of post-EPBD pancreatitis might be related to the duration of balloon dilation 13 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attributed the lower incidence of long-term stone recurrence and cholangitis in the EPBD group compared with that in the EST group to papillary function preservation [23][24][25]. In contrast, the risk of PEP has been reported to be higher than that of EST [23][24][25]35].…”
Section: Discussionmentioning
confidence: 99%
“…As EST involves an incision of the main papilla, there is a risk of perforation and bleeding. Moreover, sphincter of Oddi function disruption could cause bacterial invasion and growth in the bile ducts and reflux of digestive juices [20][21][22], which are believed to be factors in bile duct stone recurrence [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation